Digital Transformation of School Academic Management: A Case Study of an Indonesian Islamic Secondary School - Lutfia Richa Ayu Mustika; Nurkolis; Rosalina Br Ginting (Universitas Pendidikan Mandalika, 2026)
This study aims to describe the implementation of academic digitalization in the learning process at MA Negeri 2 Pati, with a focus on lesson planning, instructional delivery, and learning evaluation. A qualitative phenomenological approach was employed, involving fifteen purposively selected participants, including teachers and students. Data were collected through in-depth interviews, classroom observations, and document analysis. Data analysis followed an interactive approach consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that academic digitalization at MA Negeri 2 Pati has been implemented in a systematic and integrated manner. Digital tools are utilized in lesson planning, the deployment of digital learning platforms, interactive learning media, and digital-based assessment systems. This implementation positively contributes to learning effectiveness, assessment transparency, and the enhancement of academic service quality. The study highlights that the success of academic digitalization strongly depends on human resource readiness and sustained institutional support, including teacher professional development programs, adequate digital infrastructure, and policies that promote the integration of technology in learning activities.